Application of STAD Model Cooperative Learning To Improve Mathematics Learning Activities of Grade VI Students of SDN XI No. 40 Blimbing, Malang Regency - Antonio Guterres (Green Publisher Indonesia, 2024)
The implementation of education in schools makes various kinds of lessons to students that must be taken in realizing their ideals. The subjects received and taught to students must be developed and improved in accordance with changes in the school curriculum. The purpose of learning mathematics is expected that students are able to provide knowledge to learn and understand mathematical concepts and be able to apply scientific methods that provide process skills to solve problems in everyday life. Based on research conducted by researchers for two weeks in the field from the 03rd to the 15th, researchers managed to collect some data that the number of samples studied was 26 students in a column and read the pressure in the table of the average value r product moments with a signification level of 5% we will find the number 0.388. This number shows the signification limit number, while the average calculated value of 0.8915 means that the relationship between the learning outcomes of cooperative students and non-cooperative groups through the STAD model cooperative learning is quite good. Because the calculated value obtained by r = 0.8915 means that jau is above the signification limit of 0.388. According to the results of the data analysis obtained, the relationship between the learning outcomes of cooperative students with non-cooperative groups with the cooperative learning strategy of the STAD model is very significant between the learning outcomes of cooperative students of group X with the learning outcomes of non-cooperative students of group Y.